Determination of the efficiency of shot blasting of metal surfaces - Goryk Оleksii; Brykun, Oleksandr; Kalashnykov, Oleg; Buchynskyi, Andrii (Technology audit and production reserves, 2025)
The object of this research is the process of transformation of kinetic energy of the attacking air-abrasive torch in the process of dynamic impact on metal surfaces of products during their shot blasting. The importance of the research is due to the need to solve the problem of increasing the efficiency of the technological process of preparing metal surfaces of products by shot blasting for the subsequent application of protective, stable non-metallic coatings. In the work, based on the energy balance of the “shot-obstacle” system, a method for determining the efficiency coefficient of the shot blasting surface preparation process was developed, which was associated with the torch energy recovery coefficient. The relationship of the coefficients with the potential energy of the surface layer accumulated in the process of elastic deformation was established. The depth of the hole formed by the shot on the surface of the attacked body was taken as a measure of this energy. When determining the depth of the hole, the deformation of an elementary cylindrical element clamped in the surface layer of the attacked body was considered, the dimensions of which are compatible with the dimensions of the elastic deformation hole. The classical recovery coefficient is not a characteristic criterion for revealing the physical aspects of the complex multifactorial shot blasting process. The ease of application in practical calculations, especially when establishing the productivity of the process, prompts the search for improving the methods of its determination, since the existing models of an ideal impact in this case are not capable. This coefficient at average attack speeds of 100–120 m/s and angles of 40° < a < 70° turned out to be 15–20% less than the classical one. The obtained research results can be used to increase the productivity of the shot blasting process of products of the defense, agricultural, machine-building, chemical, aviation and other industries.